Dynamics Of Employee Organizational Commitment Reviewed from Role Conflict - Ardhana, Daniel Evan; Wibowo, Doddy Hendro (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Role conflict in sales marketing employees can potentially cause an employee to have low organizational commitment, resulting in failure to follow processes, inconsistent and inconsistent with what is expected by the company where they work. The purpose of this research is to examine the relationship between role conflict and organizational commitment in sales marketing employees. This research uses quantitative research methods. The sampling technique used was purposive sampling. The number of participants was 57 respondents. The research results show that the Pearson correlation value is -0.577 with sig. = 0.000 (p < 0.05). This means that there is no relationship between role conflict and organizational commitment in sales marketing employees. The implication of this research is that there needs to be intervention to reduce role conflict in employees so that it forms organizational commitment. Role conflict pada karyawan bagian penjualan (sales marketing) bisa berpotensi menyebabkan seorang karyawan memiliki organizational commitment yang rendah sehingga menyebabkan kegagalan dalam mengikuti proses, inkonsisten dan tidak sesuai dengan apa yang diharapkan oleh perusahaan tempatnya bekerja. Tujuan dari penelitian ini untuk menguji hubungan role conflict dengan organizational commitment pada karyawan bagian penjualan (sales marketing). Penelitian ini menggunakan metode penelitian kuantitatif. Teknik pengambilan Sampel yang digunakan adalah purposive sampling. Jumlah partisipan sebanyak 57 responden. Hasil penelitian menunjukkan bahwa nilai pearson correlation sebesar -0,577 dengan sig. = 0,000 ( < 0,05). Hal ini berarti bahwa tidak terdapat hubungan antara role conflict dengan organizational commitment pada karyawan bagian penjualan (sales marketing). Implikasi dari penelitian ini yaitu perlu ada intervensi terhadap role conflict pada karyawan agar rendah sehingga membentuk organizational commitment